In vitro and In silico studies of interactions of cathinone with human recombinant cytochrome P450 CYP(1A2), CYP2A6, CYP2B6, CYP2C8, CYP2C19, CYP2E1, CYP2J2, and CYP3A5 - Sharoen Lim, Yu Ming; Jason Loo, Siau Ee; Mustafa, Alshagga; Mohammed Abdullah, Alshawsh; Chin Eng, Ong; Yan, Pan (Elsevier B.V., 2022)
Cathinone is the psychostimulatory major active ingredient of khat (Catha edulis Forsk) and are often co-abused with alcohols and polydrugs. With the increased consumption of khat and cathinones on a global scale, efforts should be channelled into understanding and minimising the excruciating effects of possible khat-drug interactions. This study aimed to determine the in vitro inhibitory effects of cathinone on CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C19, CYP2E1, CYP2J2 and CYP3A5 and the in silico identification of their type of interactions and residues involved. The activities of CYP1A2, CYP2A6, CYP2B6, CYP2C8, CYP2C19, CYP2E1, CYP2J2 and CYP3A5 were examined by fluorescence based assays using recombinant cDNA-expressed human CYPs in Vivid® P450 screening kits. Cathinone reversibly inhibited CYP1A2, CYP2A6 and CYP3A5 via competitive, uncompetitive and noncompetitive modes with inhibition constant (Ki) values of 57.12, 13.75 and 23.57 µM respectively. Cathinone showed negligible inhibitory effects on CYP2B6, CYP2C8, CYP2C19, CYP2E1 and CYP2J2. Cathinone showed negligible time dependent inhibition on all 8 CYPs. Docking studies was performed on cathinone with CYP1A2, CYP2A6 and CYP3A5 following their inhibition in vitro. Cathinone is bound to a few key amino acid residues in the active sites while π-π interactions are formed in aromatic clusters of CYP1A2 and CYP3A5. These findings offer valuable reference for the use of cathinones and khat when combined with therapeutic drugs that are metabolised by CYP enzymes especially patients on medications metabolised by CYP1A2, CYP2A6 and CYP3A5.